(untitled) (Research, Society and Development, 2022)
Candida is a fungus that makes up the normal microbiota of an organism, and can become pathogens under immunosuppression. Candida albicans is the largest representative, as it is more prevalent in both normal and pathological processes. Thus, the present work has the general objective of evaluating the profile of women predisposing to the development of vulvovaginal candidiasis. This present study is based on a literature review, scientific articles indexed in Google Scholar, Scielo, Bireme and LILACS databases were used to compose the bibliographic research. 79 articles were initially identified after examining the content and certifying their relationship with the theme, a total of 59 articles were excluded, leaving 20 journals. In the results, it was evident that the profile of women most vulnerable to developing candidiasis, inadequate hygiene can be a contributing factor to vaginal contamination, including some sense of anal hygiene felt in the vagina, fecal residue in panties, as well as factors that metabolic imbalance, high-carbohydrate diet, as well as certain medications.